Retrograde (fundus first) Laparoscopic Cholecystectomy in Situs Inversus Totalis - Elbeshry, Turky Maeed (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2012)
Situs inversus totalis (SIT) is an uncommon anomaly characterised by transposition of organs to the opposite side of the body in a mirror image of normal. It may cause difficulties in the diagnostic and therapeutic management of abdominal pathology due to the mirror-image anatomy. We report the management of a case of symptomatic cholilithiasis with emphasis on its surgical technique.